Serological and molecular study of 20 ABO subgroup samples in Shenyang, including identification of 2 ABO new alleles - Xu ZHANG; Xiaofeng LI; Zuren ZHOU; Xuying HUANG; Lichun LI; Jianping LI (Zhongguo shuxue zazhi, 2022)
Objective To study the serological characteristics and genetic background of 20 samples with ABO blood group discrepancies in Shenyang. Methods Serological test, polymerase chain reaction-sequence specific primer (PCR-SSP) and sequencing of the full coding of ABO gene and the Intron 1 were conducted in 20 samples with ABO blood group discrepancies. Results Ten subtypes (Am, Bw, Bx, B3,, A2B, AxB, A2Bw, A2Bx, AwB and ABw) were detected in 20 samples, with AB subtype as the dominant. Sixteen ABO alleles were found, including 5 common alleles (A1.01, A1.02, B. 01, O. 01.01 and O. 01.02), nine rare alleles (AW.37, BW.03, BW.08, B3.07, cisAB.02, cisAB.03, cisAB.06, BA.04 and O. 01.04) and two novel alleles (AM.03 and cisAB.07). The AM.03 allele had a nucleotide change at position 912 (C to A) compared with A1.02 allele, which resulted in an amino acid substitution (S304R). The cisAB.07 allele was observed a missense mutation at position 797 (T to C) which resulted in an amino acid substitution (M266R) compared with B. 01 allele. The serologic had been changed, and both A antigen and B antigen were expressed. Conclusion The study revealed the genetic background of 20 samples with ABO blood group discrepancies, and two new alleles as ABO*AM.03 (912 C to A) and ABO*cisAB.07 (797 T to C) were first reported.